2010
DOI: 10.1088/0266-5611/26/7/074008
|View full text |Cite
|
Sign up to set email alerts
|

On the imaging of thin dielectric inclusions buried within a half-space

Abstract: Motivated from the application area of imaging of anti-personnel mines completely embedded in the homogeneous medium, the problem of noniterative imaging of thin dielectric inclusions buried within a dielectric halfspace is considered. For that purpose, an imaging algorithm operated at several frequencies is proposed. It is based on the asymptotic expansion formula of the scattering amplitude in the presence of the inclusions. Various numerical examples illustrate how the method behaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 17 publications
(42 reference statements)
2
70
0
Order By: Relevance
“…, M , and of small magnitude at x ∈ R 2 \Γ. Unfortunately, image function (8) at single frequency offers an image with poor resolution [3,23] (also see Figure 4). In order to improve the imaging performance, we suggest a normalized image function at several frequencies {ω f : f = 1, 2, .…”
Section: Non-iterative Multi-frequency Imaging Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…, M , and of small magnitude at x ∈ R 2 \Γ. Unfortunately, image function (8) at single frequency offers an image with poor resolution [3,23] (also see Figure 4). In order to improve the imaging performance, we suggest a normalized image function at several frequencies {ω f : f = 1, 2, .…”
Section: Non-iterative Multi-frequency Imaging Algorithmmentioning
confidence: 99%
“…Now, we end this section with the following example. Throughout some results in [4,23], it has been observed that MUSIC-type algorithm yields poorer results under the limited range of incident and observation directions. However, the proposed imaging algorithm is available for only a limited range of incident and observation directions.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…To find a good initial guess, alternative non-iterative reconstruction algorithms have been developed, such as the MUltiple SIgnal Classification (MUSIC)-type algorithm [5,23,25], linear sampling method [8,12], topological derivative strategy [3,6,18,21,22], linear-δ, vector and multipolarized approaches [29,30], and the multifrequency based algorithm such as Kirchhoff and subspace migrations [2,4,15,19,20,24]. Among them, although the multi-frequency based subspace migration has exhibited potential as a non-iterative imaging technique, a mathematical identification of its structure needs to be performed for its heuristical applications, which is the motivation behind.…”
Section: Introductionmentioning
confidence: 99%
“…, M . Therefore, W(r; ω) will plots peaks of magnitude of 1 at r = r m ∈ Σ m , and of small magnitude at r / ∈ Σ m (see [4,19,20,24]). Complete algorithm is summarized in Algorithm 1.…”
Section: Introduction To Subspace Migrationmentioning
confidence: 99%